2007
DOI: 10.1002/yea.1542
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of hirudin degradation by deleting the KEX1 gene in recombinant Pichia pastoris

Abstract: Our previous study on recombinant hirudin production in Pichia pastoris demonstrated that, although the total productivity of hirudin was fairly high, its degradation was still severe, even if many engineering methods were applied to improve cell viability and reduce the release of intracellular proteinases. In this work, a pop-in/pop-out method, replacing the auxotrophic marker ARG4 gene with the resistant marker sh ble gene, was used to delete the KEX1 gene to reduce hirudin degradation in P. pastoris GS115H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Proteolysis may occur either during vesicular transport of recombinant protein by secretory pathway-resident proteases (Werten and de Wolf 2005; Ni et al 2008) or in the extracellular space by proteases being secreted, cell wall-associated (Kang et al 2000) or released into the culture medium as a result of cell disruption during high cell density cultivation (Sinha et al 2005). Different strategies have been employed to address the proteolysis problem, namely, modifying fermentation parameters (pH, temperature and specific growth rate), changing the media composition (rich medium, addition of casamino acids or peptone as competing substrates), lowering the salt concentration and addition of soytone (Zhao et al 2008), applying protein engineering strategies (Gustavsson et al 2001) and engineering of the expression host to obtain protease-deficient strains (reviewed by Idiris et al 2010 and Macauley-Patrick et al 2005).…”
Section: Host Strain Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteolysis may occur either during vesicular transport of recombinant protein by secretory pathway-resident proteases (Werten and de Wolf 2005; Ni et al 2008) or in the extracellular space by proteases being secreted, cell wall-associated (Kang et al 2000) or released into the culture medium as a result of cell disruption during high cell density cultivation (Sinha et al 2005). Different strategies have been employed to address the proteolysis problem, namely, modifying fermentation parameters (pH, temperature and specific growth rate), changing the media composition (rich medium, addition of casamino acids or peptone as competing substrates), lowering the salt concentration and addition of soytone (Zhao et al 2008), applying protein engineering strategies (Gustavsson et al 2001) and engineering of the expression host to obtain protease-deficient strains (reviewed by Idiris et al 2010 and Macauley-Patrick et al 2005).…”
Section: Host Strain Developmentmentioning
confidence: 99%
“…PEP4 encodes a major vacuolar aspartyl protease which is able to activate itself as well as further proteases such as carboxypeptidase Y ( PRC1 ) and proteinase B ( PRB1 ). The use of protease-deficient strains other than the above mentioned (e.g., yps1 , kex1 , kex2 ) was reported with variable success (Ni et al 2008; Werten and de Wolf 2005; Wu et al 2013; Yao et al 2009). A general conclusion from these studies is that in many cases several proteases are involved in degradation events and, therefore, it is not an easy task to optimize protein expression by knocking out just a single one.…”
Section: Host Strain Developmentmentioning
confidence: 99%
“…There are reports in the literature where the KEX1 gene has been disrupted to express full length proteins in P. pastoris. When Hirudin was expressed in P. pastoris it was found that the molecule had degraded products where up to three amino acids were clipped from the C-terminus [25]. When human and murine endostatin were expressed in P. pastoris the C-terminal lysine was clipped [13].…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of proteins in P. pastoris depends critically on growth conditions (Solà et al , 2007), such as temperature, carbon source (Ni et al , 2008) and oxygen (Verbelen et al , 2009), which have been proven to be cell type-specific and varied depending on the product that is generated, so it has not yet been achieved a specific method, like biomarkers, to determine the effects of these conditions to find the optimal parameters for each model. Among the adverse consequences caused by disregard the effects of these parameters on the cultivation of yeast, temperature conditions would affect the expression of the transcription factor known as factor of response to heat stress (HSF-1) (Gasser et al , 2007), so it would regulate HSP-70 expression.…”
Section: Introductionmentioning
confidence: 99%